The right of EU citizens to vote and stand in parliamentary elections in the member state of their residence - Danikowski, Marek (The Opole Studies in Administration and Law, 2016)
The right of EU citizens residing in another Member State, to vote and stand in elections to the European Parliament is a major achievement of the European democracy. In the light of EU citizens’ still insufficient knowledge concerning the opportunities and benefits brought in by this right, it is worth making this institution more familiar to themin a straightforward way, at the same time balancing criticism towards the idea of the EU.